Effect of Kaolin and Phonolite Particulates Addition on Some Physical Properties of Glass−Fiber Composites: Effect of Kaolin and Phonolite Particulates Addition on Some Physical Properties of Glass−Fiber Composites - Ballem, Mohamed; Aldarwish, Mustafa; Alnairi, Ahmed; Endisha, Mohamed (Journal of Pure & Applied Sciences, 2025)
this research, some physical properties of a fiber-reinforced composite material with a modified polymer matrix by adding of natural fillers were studied. By using of hand lay-up method three groups of polymer-based composite specimens contained a fixed weight percentage of chopped glass fiber were fabricated. The first group was prepared without any additive particles to serve as a reference, while the other two groups were prepared by incorporating the kaolin and phonolite particles, respectively, into the polyester resin (at weight percentage of 10% and particle size of 75 to 125 μm). The physical properties of the specimens were investigated by carrying out several tests according to ASTM standards to determine the effect of these fillers on the relative density, true density, void content, and fire-resistance properties of the prepared composites. In addition, the effect of distilled water and seawater on the weight and dimensions (thickness swelling) of the specimens were evaluated. The obtained results showed that adding phonolite and kaolin particles to the composite material had a minor effect on all the studied properties. For instance, the density increased by only 3%, while the percentage of weight change due to water absorption did not reach 0.2% for all studied specimens. The Fire-resistance of the materials shows a relatively improvement for the specimens containing kaolin and phonolite fillers, while the dimensions of all the composites were not affected at all. The study concluded that adding of some locally available natural materials as fillers during the manufacturing process of fiber-reinforced composite materials did not affect their physical properties that distinguish them from other materials such as dimensional stability and high ratio of strength to weight, and that making them more suitable for many engineering applications.